Criticality assessment of energy infrastructure - Augutis, Juozas; Jokšas, Benas; Krikštolaitis, Ričardas; Žutautaitė, Inga (Technological and Economic Development of Economy, 2014)
After the last major accidents in the energy sector of the last decade (USA and Canada (2003), India (2012), Russian-Ukrainian (2009)), energy infrastructure criticality assessment has become one of the most important issues. It has become the topical subject of the economy and national security in all countries. There is no single measure unit for the assessment of critical infrastructure with respect to “interdependency” among critical infrastructure sectors. This paper proposes to use criticality of infrastructure element as a measure to assess the importance of considered element to the normal activity of all sectors of infrastructure. The pilot numerical simulation of heat and electricity infrastructure was performed to demonstrate the implementation of the application of developed method for the assessment of infrastructure functionality and criticality.